Laudian Foxe-hunting? William Laud and the status of John Foxe in the 1630s - Nussbaum, Damian (Studies in church history, 1997)
When the prosecutors of William Laud were seeking damning evidence against the Archbishop, they seized upon the fate of John Foxe’s Acts and Monuments in the 1630s. They produced a catalogue of abuses, occasions on which Laud had attacked, impugned, or banned the volumes. In his report of the trial, Prynne gave these cases of Foxe-hunting an important position, directly after the accusation that Laud had hindered the distribution of Bibles. The prominence given to Foxe, and the close association with the Bible, were typical of the ways the martyrologist was handled in the early seventeenth century, and tell us much about the regard in which he was held within the English Church. His Book of Martyrs had attained the status of a quasi-biblical text. His works, invoked with an almost scriptural reverence, were appealed to as an unquestionable authority on matters of ecclesiastical history and Protestant tradition.